Photosynthetic and yield performance of rice (Oryza sativa) genotypes under low temperature condition in hills - KUMAR, PRAMOD (The Indian Journal of Agricultural Sciences, 2014)
A field experiment with 15 genotypes of rice (Oryza sativa L.) was carried out during the rainy season of 1999 and 2000 to understand the photosnthetic basis of yield under low temperature in hills. Exposure of rice genotypes to low temperature conditions during reproductive phase was made by altering the dates of sowing, ie normal and 1 month late. The rate of photoynthesis (R = 0.584*) and canpy photosynthesis (R + 0.830**) estimated during grain-filling phase showed significant positive correlation with grain yield under normal planting and poor association under low temperature condition, ie late planting. Rates of canopy photosynthesis during the early phase of plant development under both plantings were found almost similar, ie no reduction in nursery bed and 2.71% at vegetative stage. A significant reduction in rates of photosynthesis (36.68%), canopy photoynthesis (44.14%), transpiration (29.30%), stomatal conductance(76.80%) and level of photosynthetic pigments (52.51%), nitrate reductase (NR) activity (51.61%) was observed at grain-filling stage under low temperatute condition. Besides, a reduction in the grain-filling rate was also noted under late planting due to low temperature. Harves index (HI) showed the significant positive association with grain yield (R + 0.772**) under low temperature condition. only, which in turn indicated that the low temperature reduced the partitioning of photo-assimilates which resulted in poor yield. A significant relationship of grain sterility (r = -0.836**), harvest index (R = 0.929**), panicle weight (R = 0.574*), NR activity (R = 567*), anthocyanins content (R = 561*) with cold-tolerance efficiency was observed.